Petroleum Production – United States - Petroleum Development in Illinois and Indiana during 1928 - Gail F. Moulton (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1929)
The production of petroleum in Illinois in 1928 was approximately 6,500,000 bbl., a decline of about 500,000 bbl. from the previous year and of about 1,500,000 bbl. from 1924. Production increased about 200,000 bbl. in Indiana to slightly less than 1,000,000 bbl. Production for 1929 is estimated at approximately 6,000,000 bbl. for Illinois and 1,000,000 bbl. for Indiana. Illinois Because production from most of the wells in the state has declined to a small daily average and the low prices for crude oil discouraged wildcatting, the number of wells drilled fell below that for any previous year since the development of commercially important production in the state. The Ohio Oil Co. discovered a pool of apparent commercial importance in southwestern Illinois near Dupo, in St. Clair County, and favorable showings of oil were encountered in a well in southeastern Illinois, near Harrisburg in Saline County. New production from the Dupo area is expected to check the rate of decline for the state. Thc following tablel summarizes field developments for 1927 and 1928 (for important detail by counties see notes at foot of table): 1027 1928 Completions........................................... 162 145a Initial production, bbl.................................. 2244 1840b Dry holes........................................,.... 66 58" Gas well completions................................... 13 8d 0111 wells abandoned.................................... 45" a Crawford, 44; Lawrence, 28; Wabash, 40. b Crawford, 501; Lawrence, 403; St. Clair, 165 (4 completions); Wahash, 668. o Crawford, 12; Wabash, 19. d Crawford, 6. b Lawrence, 21; Wabash, 15. The discovery well in the Dupo field in St. Clair County, produced about 150 bbl. per day from the Trenton lime at 660 ft. It is located in a northern extension of the Columbia-Waterloo anticline on which the Waterloo pool was developed in 1921. The best information on the.